Overexpression of CXCL12 chemokine up-regulates connexin and integrin expression in mesenchymal stem cells through PI3K/Akt pathway. (August 2013) - Xiaowei, Chi; Jia, Meng; Xiaowei, Wu; Yina, Zhang
Abstract: Mesenchymal stem cells offer several potential advantages over other types of stem cells for cardiac repair. Nevertheless, poor survival of donor cells is one of the major concerns that hampers a better prognosis. Integrins, which involved in cell/extracellular matrix (ECM) interaction and connexins (Cxs), with a dual role as an anti-apoptotic and gap-junctional protein, can effectively resolve this issue. CXCL12, a member of the chemokine CXC subfamily, may play a role in stem cell survival and proliferation. CXCL12 activates several signaling pathways in stem cells, particularly the survival kinase, PI3K/Akt, which is also an important mediator of integrins and Cxs. Based on these characteristics of CXCL12, we investigated the potential of CXCL12 overexpression to induce integrin and connexin expression via PI3K/Akt pathway. Mesenchymal stem cells were transfected with adenovirus for increasing CXCL12 secretion. Membranous integrin and Cx expression as well as Akt expression levels were evaluated using Western blot analysis. Transfection resulted in increased CXCL12 in situ. Increased CXCL12 elevated membrane Cx43, Cx45, and integrin αVβ3 expression, as well as Cx phosphorylaton, which was activated by PI3K/Akt pathway. This mechanism may serve to improve mesenchymal stem cell viability in host tissue.